Periodic Vortex Streets and Complex Monodromy - Hemery, A.D.; Veselov, P.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
The explicit constructions of periodic and doubly periodic vortex relative equilibria using the theory of monodromy-free Schrödinger operators are described. Several concrete examples with the qualitative analysis of the corresponding travelling vortex streets are given.